Towards Electronic Democracy: The Impact of Technological Change on the Official Information Act 1982 - White, Jessica (Victoria University of Wellington Law Review, 2008)
The paper considers the impact of recent technological advancements on the law and policy of the Official Information Act 1982. As the capacity and potential of technology increases, the ability to store, retrieve, and disseminate information could add immense value to the purposes and operation of the Act. However, there are two substantial difficulties with the technological changes. First, there are insufficient efforts to improve access to technology for certain segments of society. Second, co-ordination between initiatives to improve government information management systems have so far proved ineffective. These two problems pose substantial threats to the usefulness of the new technology. Consequently, the paper concludes by recommending that a co-ordinated, educational approach led by central government will ensure that the Act’s benefits for citizens are enhanced by technological change, rather than undermined by it.